A temperature‐controlled single‐crystal growth cell for the in situ measurement and analysis of face‐specific growth rates. Issue 2 (28th March 2019) - Turner, T. D.; Nguyen, T. T. H.; Nicholson, P.; Brown, G.; Hammond, R. B.; Roberts, K. J.; Marziano, I.
Abstract : This article presents the design, mechanical drawings and outline methodology for the construction and use of a single‐crystal growth cell; its application to determine face‐specific growth rates and mechanisms in seeded or unseeded experimental conditions is highlighted. Abstract : The design and construction of a growth cell for the precision measurement of face‐specific single‐crystal growth rates are presented. Accurate mechanical drawings in SolidWorks of the cell and individual components are provided, together with relevant construction models. A general methodology for its use in the measurement of single‐crystal growth rates and their underpinning growth mechanism is presented and illustrated with representative data provided for the crystal growth of the {011} and {001} faces of RS ‐ibuprofen single crystals grown in ethanolic solutions. Analysis of these data highlights the utility of the methodology in morphological model development and crystallization process design.